Rotifera pada Area Bekas Tambang Emas di Kabupaten Sawahlunto Sijunjung - Silvi Susanti; Abizar Abizar (BIO-SITE |Biologi dan Sains Terapan, 2016)
Rotifers is one of many zooplankton commonly found in freshwater. As the heterotrophic animal rotifers were able to recycle organic material so that the rotifers could live in mined areas or kolong. An abundance of rotifers and chemical physics factor measurements taken at six stations using the method descriptive survey conducted to determine the relationship with kolong’s age. The results showed that the station over the age of 12 months have been located in waters climactic conditions.